2020
DOI: 10.1186/s12987-020-00212-5
|View full text |Cite
|
Sign up to set email alerts
|

A face-to-face comparison of claudin-5 transduced human brain endothelial (hCMEC/D3) cells with porcine brain endothelial cells as blood–brain barrier models for drug transport studies

Abstract: Background: Predictive in vitro models of the human blood-brain barrier (BBB) are essential in early drug discovery and development. Among available immortalized human brain capillary endothelial cell lines (BCECs), the hCMEC/ D3 cell line has become the most widely used in vitro BBB model. However, monolayers of hCMEC/D3 cells form only moderately restrictive barriers, most likely because the major tight junction protein, claudin-5, is markedly downregulated. Thus, hCMEC/D3 monolayers cannot be used for vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 67 publications
5
17
0
Order By: Relevance
“…TEER values were comparable in all cell lines, reaching maximal values of ~ 13–16 Ω cm 2 when measured with an EndOhm chamber. For hCMEC/D3 cells, these low TEER values were comparable to values reported in the literature when using an epithelial Volt-Ohm meter (EVOM) coupled to an EndOhm chamber for TEER measurements [ 43 , 47 ], whereas TEER measurements with chopstick electrodes result in significantly higher values [ 21 , 43 , 48 ]. When TEER was measured with an EndOhm chamber in primary rBCECs, values were in the range of 80–140 Ω cm 2 (Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…TEER values were comparable in all cell lines, reaching maximal values of ~ 13–16 Ω cm 2 when measured with an EndOhm chamber. For hCMEC/D3 cells, these low TEER values were comparable to values reported in the literature when using an epithelial Volt-Ohm meter (EVOM) coupled to an EndOhm chamber for TEER measurements [ 43 , 47 ], whereas TEER measurements with chopstick electrodes result in significantly higher values [ 21 , 43 , 48 ]. When TEER was measured with an EndOhm chamber in primary rBCECs, values were in the range of 80–140 Ω cm 2 (Fig.…”
Section: Resultssupporting
confidence: 81%
“…In the present study, the CETA assay was used to determine the flux of the radiolabeled Pgp substrate [ N -methyl- 3 H]N-desmethyl loperamide ([ 3 H]dLop) across hCMEC/D3- MDR1 -EGFP and RBE4- MDR1 -EGFP monolayers. Although Kannan et al [ 42 ] have shown that [ 3 H]dLop is trapped in lysosomes, this does not restrict its use for studying Pgp-mediated vectorial drug transport in BCECs, as demonstrated recently by us in primary cultured porcine BCECs [ 43 ]. Cells were grown on permeable ThinCert® filter supports (12-well, 0.4 µm pore size, PET, Greiner Bio-One).…”
Section: Methodsmentioning
confidence: 99%
“…Abcb1 , which encodes MDR1/P‐gp, is involved in BBB transporter function and Aβ clearance in the brain 31,32 . As brain uptake is often restricted by the active efflux transporter ABCB1, we evaluated the effect of CD147 ablation on ABCB1 by Rho123 uptake assay 33 . We found a reduction in Rho123 accumulation in BECs isolated from EC‐KO mice (Figure 5E,F), confirming that endothelial CD147 deficiency resulted in an increase in ABCB1 expression.…”
Section: Resultssupporting
confidence: 52%
“…Moreover, the TEER values measured in vivo have been reported to be as high as 5900 Ω·cm 2 [ 33 ]. Even the human brain endothelial cell lines (hCMEC/D3) used in co-culture with astrocytes have yielded relatively low TEER value and less than 500 Ω·cm 2 TEER value is measured in currently available in vitro models [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. In this study, we demonstrated that a microfluidic platform can allow the exposure of cells to dynamic conditions that provide 5 dyne/cm 2 shear stress simulation.…”
Section: Resultsmentioning
confidence: 99%